Maghemite decorated with ultra-small palladium nanoparticles (γ-Fe2O3–Pd): applications in the Heck–Mizoroki olefination, Suzuki reaction and allylic oxidation of alkenes. Issue 8 (23rd December 2015) - Rathi, Anuj K.; Gawande, Manoj B.; Pechousek, Jiri; Tucek, Jiri; Aparicio, Claudia; Petr, Martin; Tomanec, Ondrej; Krikavova, Radka; Travnicek, Zdenek; Varma, Rajender S.; Zboril, Radek
Abstract : γ-Fe2 O3 –Pd NPs for Heck, Suzuki and allylic oxidation reaction under milder conditions. Abstract : A nanocatalyst comprising ultra-small Pd/PdO nanoparticles (<5 nm) supported on maghemite was prepared by a co-precipitation protocol using inexpensive raw materials and was deployed successfully in various significant synthetic transformations, namely the Heck–Mizoroki olefination (up to 95%), the Suzuki reaction (60–95%), and the allylic oxidation of alkenes under milder conditions. The chemical nature, morphology, size, and loading of palladium nanoparticles over the magnetic support were studied by TEM/EDX, HAADF-STEM chemical mapping, XPS, AAS, and in-field 57 Fe Mössbauer spectroscopy. The cost-effective catalyst could be easily separated from the reaction mixture by using an external magnet and reused four times without any loss of activity; chemical stability and recyclability aspects of the catalyst were investigated.